West Nile Virus Temperature Sensitivity and Avian Virulence Are Modulated by NS1-2B Polymorphisms. - Elizabeth A Dietrich; Stanley A Langevin; Claire Y-H Huang; Payal D Maharaj; Mark J Delorey; Richard A Bowen; Richard M Kinney; Aaron C Brault (Public Library of Science (PLoS), 2016)
West Nile virus (WNV) replicates in a wide variety of avian species, which serve as reservoir and amplification hosts. WNV strains isolated in North America, such as the prototype strain NY99, elicit a highly pathogenic response in certain avian species, notably American crows (AMCRs; Corvus brachyrhynchos). In contrast, a closely related strain, KN3829, isolated in Kenya, exhibits a low viremic response with limited mortality in AMCRs. Previous work has associated the difference in pathogenicity primarily with a single amino acid mutation at position 249 in the helicase domain of the NS3 protein. The NY99 strain encodes a proline residue at this position, while KN3829 encodes a threonine. Introduction of an NS3-T249P mutation in the KN3829 genetic background significantly increased virulence and mortality; however, peak viremia and mortality were lower than those of NY99. In order to elucidate the viral genetic basis for phenotype variations exclusive of the NS3-249 polymorphism, chimeric NY99/KN3829 viruses were created. We show herein that differences in the NS1-2B region contribute to avian pathogenicity in a manner that is independent of and additive with the NS3-249 mutation. Additionally, NS1-2B residues were found to alter temperature sensitivity when grown in avian cells.